Bayesian networks for probabilistic inference and decision analysis in forensic science - Taroni, Franco; Biedermann, Alex.; Bozza, Silvia; Garbolino, Paolo; Aitken, Colin (Chichester, West Sussex : Wiley, 2014)
'The aim is to offer theoretical and practical elements to help solve the following questions'--
Includes bibliographical references and index.
Keywords: Bayesian statistical decision theory -- Graphic methods; Uncertainty (Information theory) -- Graphic methods; Forensic sciences -- Graphic methods